Answer:
Step-by-step explanation:
11:35 or b
I did it digitally on my iPad hope it helps please mark me brainliest
Answer:
y = -4
Step-by-step explanation:
12y + 4 = 8y-12
Subtract 8y from each side
12y - 8y +4 = -12
4y +4 = -12
Subtract 4 from each side
4y +4-4 = -12 -4
4y = -16
Divide by 4
4y/4 = -16/4
y = -4
<span>Simplifying
4x2 + 8xy + 4y2
Reorder the terms:
8xy + 4x2 + 4y2
Factor out the Greatest Common Factor (GCF), '4'.
4(2xy + x2 + y2)
Factor a trinomial.
4((x + y)(x + y))
Final result:
4(x + y)(x + y)</span>